Communication Process in Field Trip as a Learning Method for PAUD Children in Bandung - Ditha Prasanti; Kismiyati El Karimah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This article is the result of research conducted by the author at one of the Foundation for Early Childhood Education (ECE) in the city of Bandung. Starting from the hectic variety of field trip activities organized by each PAUD institution, there were complaints from parents of students regarding funds that had to be spent if the field trip was out of town, and other pros and cons in aspects of PAUD children's learning methods. The results of the research conducted show as follows: 1) field trip activities as an effective learning method used by teachers in the gross motor learning process in the PAUD; 2) the communication process carried out in field trip activities consists of communicator aspects, messages given, and the media used , and the result or effect in the field trip.